2013
DOI: 10.2478/bvip-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Listeria Monocytogenes Isolated from Slaughtered Cattle and Beef Meat

Abstract: A total of 135 L. monocytogenes strains isolated from slaughtered cattle and beef meat were tested by the pulsed field gel electrophoresis (PFGE). The AscI restriction analysis revealed a genetic heterogeneity among investigated isolates since 31, 9, and 35 profiles were distinguished among hide, carcass, and meat strains, respectively. The PFGE profiles of the isolates were also analysed in relation to serotypes, virulence genes, and antimicrobial resistance. It was shown that strains displaying the same PFGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…monocytogenes with Listeria pathogenicity island 3 (LIPI-3) [ 21 ], and isolates from the present study exhibited 44.8% (111/248) positivity. This rate is higher than those obtained by Dmowska et al [ 60 ] and Shen et al [ 20 ], who observed that 7.4% and 12.4% of llsX -positive samples from beef and retail meat, respectively. Although all strains isolated from raw meat and quick-frozen foods contained inlA , inlC and inlJ genes, most of these strains (34/49 and 83/108) lacked the llsX gene.…”
Section: Resultscontrasting
confidence: 69%
“…monocytogenes with Listeria pathogenicity island 3 (LIPI-3) [ 21 ], and isolates from the present study exhibited 44.8% (111/248) positivity. This rate is higher than those obtained by Dmowska et al [ 60 ] and Shen et al [ 20 ], who observed that 7.4% and 12.4% of llsX -positive samples from beef and retail meat, respectively. Although all strains isolated from raw meat and quick-frozen foods contained inlA , inlC and inlJ genes, most of these strains (34/49 and 83/108) lacked the llsX gene.…”
Section: Resultscontrasting
confidence: 69%
“…The main routes of contamination for animals (especially livestock) are silage (Welchman et al, 1997) and the animals themselves. This animal carriage of L. monocytogenes in the agricultural environment can lead to contamination of animal products such as raw milk (Huntet al, 2012) or meat (Dmowska et al, 2013). Contamination of agricultural raw materials is a pathway for the pathogen to enter the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…There are many transmission paths of this bacterium among animals, between animals and man, and among people. The main source of infection for animals and humans is contaminated food, predominated by silage for animals and frozen food, meat, fish, unpasteurised milk, and dairy products for people (3,13,14).…”
Section: Introductionmentioning
confidence: 99%